2020
DOI: 10.1021/acs.biochem.0c00124
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Staphylococcus aureus Surface Protein SdrC

Abstract: Staphylococcus aureus surface proteins play important roles in host tissue colonization, biofilm formation, and bacterial virulence and are thus essential for successful host infections. The surface protein SdrC from S. aureus induces bacterial biofilm formation via an intermolecular homophilic interaction of its N2 domains. However, the molecular mechanism of how the homophilic interaction is achieved is unknown. Here, we report two crystal structures of SdrC N2N3 domains, revealing two possible homophilic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Recently, Pi and coworkers solved a dimer structure of Ca 2+ -bound SdrC and found that the VDQYT 288-292 fragment was adjacent to the Ca 2+ -binding site so that the dimer could be destroyed by Ca 2+ deficiency. Moreover, they also reported another SdrC dimer (without Ca 2+ ) that was formed in the same way as our structure (Pi et al, 2020). Although both of the research groups mentioned above reported that N2 was the only subdomain that was involved in SdrC selfassociation, we assumed that in addition to Ca 2+ -mediated dimerization the homophilic interaction between N2 and N3 may be another mechanism for SdrC biofilm formation ( Supplementary Figs.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Recently, Pi and coworkers solved a dimer structure of Ca 2+ -bound SdrC and found that the VDQYT 288-292 fragment was adjacent to the Ca 2+ -binding site so that the dimer could be destroyed by Ca 2+ deficiency. Moreover, they also reported another SdrC dimer (without Ca 2+ ) that was formed in the same way as our structure (Pi et al, 2020). Although both of the research groups mentioned above reported that N2 was the only subdomain that was involved in SdrC selfassociation, we assumed that in addition to Ca 2+ -mediated dimerization the homophilic interaction between N2 and N3 may be another mechanism for SdrC biofilm formation ( Supplementary Figs.…”
Section: Resultssupporting
confidence: 81%
“…It has been reported that gene expression of sdrC is upregulated during the shift of S. aureus from colonization to invasion, suggesting a potential role for SdrC in staphylococcal pathogenesis (Jenkins et al, 2015). Moreover, the N2 domain of SdrC has been implicated to be involved in biofilm formation through homophilic interactions in previous research (Barbu et al, 2014), but the binding details were not fully clarified (Pi et al, 2020). Here, we determined the crystal structure of the N2 and N3 domains of SdrC (SdrC-N2N3) by X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by the upregulation of genes (sdrCDE, fnbB, and some cell-wall related genes) associated with adhesion and biofilm formation in VISA. Fibronectin binding protein B (FnbBp) is a large multidomain protein encoded by fnbB (Xiong et al, 2015), while SdrCDE protect bacteria from host immune mechanisms and the effects of antibiotics (Barbu et al, 2014;Zhang et al, 2017;Pi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, interacting base components (g À s ) of a stationary substrate with a diffusing bacterium would have an increasing intermolecular charge repulsion as the distance between substrate and bacterium decreases. Such would especially be present in the non-chelated N2 domain of the surface protein (Pi et al, 2020). Second and likely to a lesser degree, a polarizable soft atom (e.g., bromine or iodine) or other polarizable moiety could allow the bacterium to remain associated with the substrate in the absence of reversible adhesion during primary colonization.…”
Section: Surface Energy Analysesmentioning
confidence: 99%
“…Because of (1) significant genetic differentiation between microorganisms and (2) the colloidal nature of microorganisms, even adhesion is a complex process that is phenotypically heterogeneous and not a single determinant process (Vissers et al, 2019). For example, the surface protein SdrC of S. aureus has been shown to use Ca 2+ -mediated chelation of the N2 domains as a primary contributor to biofilm formation; the use of a metal salt associated with the substrate may disrupt the aforementioned chelation illustrating how metal salts effectively inhibit biofilm formation (Pi et al, 2020). To further illustrate the diversity in the adhesion process, McLay et al were able to genetically alter Escherichia coli to demonstrate that the amount of fimbriation contributes to adhesion of the bacterium (McLay et al, 2018).…”
Section: Introductionmentioning
confidence: 99%